Influence of Arthrospira platensis (spirulina) as a biostimulant on the growth of Lactuca sativa L. (lettuce), Trujillo – 2024 - Aguilar Aspiros, Angie Damary; Floríndez Castro, Gianella Nicole; Diaz Ruiz, Julian Ricardo (LACCEI, 2025)
The excessive use of inorganic fertilizers in agriculture has caused harmful effects to the environment, therefore, we seek to develop alternative products that offer nutrients necessary for the development of plants without damaging the quality of the soil. For this reason, this study aimed to evaluate the effect of Arthrospira platensis as a biostimulant on Lactuca sativa L.. The research carried out is of an applied type, with an experimental design with a quantitative approach and correlational scope, the sample consisted of 16 Lactuca sativa L. seedlings. The data collection technique was observation, using the observation sheet as an instrument. The experiment was carried out in an uncontrolled environment using a completely randomized design (four treatments with four repetitions), the concentrations used were: 0.00%, 0.04%, 0.08% and 0.12%, the results were processed through ANOVA statistical analysis, evidencing that the 0.04% concentration offers the plant better morphological results, achieving greater leaf height (33.35 cm), total length (46 cm) and roots (12.35 cm), number of leaves (22), and total biomass weight (148.68 gr). In this way, it is concluded that the use of biostimulant based on Arthrospira platensis provides significant effects on the growth of Lactuca sativa L..